Safety evaluation of continuous green T intersections: A propensity scores-genetic matching-potential outcomes approach. (August 2016) - Wood, Jonathan; Donnell, Eric T.
Highlights: This paper used a propensity scores-potential outcomes framework, with genetic matching, to estimate the safety effects of the continuous green T (CGT) intersection relative to a conventional signalized T intersection. Crash modification factors (CMFs) for the CGT were developed for total, fatal and injury, and target (rear-end, angle, and sideswipe) crashes. The results show that the CMFs for all crash types were less than 1.0, indicating that the CGT intersection offers safety benefits relative to the traditional signalized T intersection. Abstract: The continuous green T intersection is characterized by a channelized left-turn movement from the minor street approach onto the major street, along with a continuous through movement on the major street. The continuous flow through movement is not controlled by the three-phase traffic signal that is used to separate all other movements at the intersection. Rather, the continuous through movement typically has a green through arrow indicator to inform drivers that they do not have to stop. Past research has consistently shown that there are operational and environmental benefits to implementing this intersection form at three-leg locations, when compared to a conventional signalized intersection. These benefits include reduced delay, fuel consumption, and emissions. The safety effects of the conventional green T intersection are less clear. Past research has been limited to small sample sizes, or utilized only statistical comparisons reported crashes to evaluate the safety performance relative to similar intersection types. The present study overcomes past safety research evaluations by using a propensity scores-potential outcomes framework, with genetic matching, to compare the safety performance of the continuous green T to conventional signalized intersections, using treatment and comparison site data from Florida and South Carolina. The results show that the expected total, fatal and injury, and target crash (rear-end, angle, and sideswipe) frequencies are lower at the continuous green T intersection relative to the conventional signalized intersection (CMFs of 0.958 [95% CI = 0.772–1.189], 0.846 [95% CI = 0.651–1.099], and 0.920 [95% CI = 0.714–1.185], respectively).